Diseño de un sistema de gestión administrativo, financiero, contable para Nov Downhole del Ecuador Cía. Ltda. filial de la red mundial National Oilwell Varco - Taco Saltos, Lida Isabel (2015)
This paper focuses on the design of a System of Administrative, Financial and Accounting Management for NOV Downhole of Ecuador Cia. Ltd. Subsidiary of the World Network National Oilwell Varco.; Prioritizing the processing of financial information from interactions between organizational departments and the starting point is an analysis of the theoretical foundation that provides the relevant characteristics concerning the administrative process: Planning, Organization, Management and Control; states and financial reasons related to accounting regulations. A situation assessment by analyzing: products and services offered, key competitors and customers, external risks and financial ratios (liquidity, activity, indebtedness and profitability) of 2013. In addition, Competitive Profile Matrix Internal (PCI) and Oportunidades Threats (POAM) for internal and external evaluation by a weighting which allows for SWOT, use arrays (Strengths-Opportunities) and vulnerability (Weaknesses-Threats) and get SWOT Factors Critical to the significant contribution of the 4 people in the financial area. The proposed management system part with the development of functional organization chart and structural addressing human talent to bond with the organizational philosophy matrices axiological principles and values to create the process map and add value to characterize the financial department, build four indicators, modeling the nine key procedures using flowcharts in BIZAGI and tools nontraditional quality management to support the development of the daily activities of finance.